The republic of emperors: Interview with Professor Franco Fornari - Rosci, Elena (Quaderni di Psicologia Clinica, 2025)
This interview with Franco Fornari, conducted by Elena Rosci and published in La Repubblica on April 15, 1983, is republished in full for readers of Quaderni di Psicologia Clinica (Journal of Clinical Psychology) for its significant historical and cultural value. Fornari – psychiatrist, psychoanalyst, president of the Italian Psychoanalytic Society from 1973 to 1978, and director of the Institute of Psychology at the University of Milan – was a centrally important author for the development of psychoanalysis and clinical psychology in Italy, with fundamental contributions to the theory of unconscious affective semiosis and to the psychoanalytic analysis of institutional, social, and political phenomena. The interview takes place at a particularly significant moment in his intellectual trajectory, coinciding with the publication of “La lezione freudiana” (The Freudian Lesson, Feltrinelli, 1983), two years before his death. The republication serves two objectives: to preserve the historical memory of the theoretical-clinical elaboration of one of the principal authors of Italian psychoanalysis, and to highlight the importance of the relationship between the development of psychological-clinical thought and scientific-professional affiliations, a central theme for the editorial line of Quaderni. Fornari’s metaphor of the “republic of emperors” reveals the necessarily situated nature of psychoanalytic knowledge within professional affiliations and in the historical, cultural, and institutional vicissitudes in which they are inscribed.
Keywords: history of psychoanalysis; Italian psychoanalysis; Franco Fornari; professional affiliations